Re-creating (hi)stories: - Anette Svensson (Educare)
In response to the challenge to educate democratic citizens and prepare them for life in a global and digital world, a teaching design that focuses on stories that re-claim a place in the literary tradition for groups of people who have been marginalised or silenced in literary classics has been developed and implemented in the upper secondary EFL classroom. The aim of this article is to analyse essays where upper secondary school students compare Anne of Green Gables to Anne with an E in order to discuss how transmedia storytelling can function as social and cultural empowerment and encourage global and critical awareness. The method is design-based research, and the data consist of 89 comparative essays that have been thematically analysed, resulting in four themes: altered mood, altered characters, added characters, and the function and effect of transmedia storytelling. The results show that the students focus on new themes and characters, which are easier to relate to. By comparing the source text to the makeover, they notice that Anne with an E sheds light on aspects which are missing in Anne of Green Gables. As they compare, they question the historical accuracy of both the source text and the makeover, thus demonstrating critical awareness.